Analisis Keragaman Genetik Klon Kelapa Sawit (Elaeis guineensis Jacq.) Berdasarkan 4 Marka RAPD (Random Amplified Polymorphism DNA) - Ana Christin Simbolon Simbolon; Mbue Kata Bangun; Lollie Agustina Putri (Universitas Sumatera Utara, 2017)
The aim of research was to analyzes genetic diversity in oil palm from clone based on RAPD markers (Random Amplified Polymorphism DNA). This research has been conducted at the laboratory of molecular genetics Faculty of Agriculture University of Sumatera utara and BioMolecular Laboratory SSPL (Socfindo Seed Production and Laboratories), Bangun Bandar, Dolok Masihul, Serdang Bedagai, Sumatera Utara, from March to August 2016. The number of samples were samples of the original palm leaf clones derived from PT. SOCFINDO and have been isolated. There was differences in bands pattern resulted from primer OPD-20, OPD-13, OPH-13, OPN-03. The size of bands was 470 – 2609 bp. Coefficients of genetic diversity and phylogenetic dendogram obtained using software Darwin5.05 which can only process 28 accessions tested. The analysis showed that accessions palm oil clones were divided into three main groups. Keywords: clones, genetic diversity, oil palm, random amplified polymorphism DNA.